Heat Transfer Augmentation Based on Twin Impingement Jet Mechanism - Abdullah, Mahir Faris; Zulkifli, Rozli; Harun, Zambri; Abdullah, Shahrir; Ghopa, Wan Aizon W.; Abbas, Ashraf Amer (International Journal of Engineering and Technology, 2018)
Much of the research interest has now been conferred to jet impingement heat transfer mechanism, particularly in cooling related to electronic equipment and automotive engine since forced convection action generates high heat transfer coefficients. The paper aims to improve the heat transfer rate at radial position at a distant from the stagnation point. This is achieved by determining the local heat transfer coefficients by considering the aluminium plate surface, which employs the twin impingement jet mechanism likewise that allows capturing the distribution associated with heat transfer characteristic near the measured surface because there is not much information regarding this topic. This article presents the experimental studies regarding jet impingement heat transfer as well as associated measurements for local heat transfer coefficient. This subsequently resulted in determining the heat transfer rate associated with the impingement aluminium plate. In this research study, nine models with different parameters has been developed where the distance from nozzle to aluminium Plate (H) equal 10, 60 and 110 mm, while the spacing between nozzles (S) equal 10, 20 and 30 mm. At Reynolds number 10,000, measurements were done, and a heat flux micro-heat sensor installed away from the stagnation point from 0 to 140 mm at radial positions, was employed to measure the heat flux of the steadily heated air jet that impinged on the aluminium surface. The local heat transfer coefficients regarding steady air jet were calculated by measuring the heat flux. Thermal data are recorded, and Graphtec GL820 multichannel data logger was employed to capture distributions of heat transfer. The best heat transfer coefficient was observed through the results from the area enclosed between aluminium plate and nozzles and the closest distance between twin nozzles, particularly in the initial 5 points at the flat, which lowering as we start to move away from the aluminium plate centre. The temperature distribution at the front of aluminium foil Fluke Ti25 was recorded with the help of an infrared thermal imager.